Peran Instagram dalam Strategi Komunikasi Politik Okta Kumala Dewi pada Pemilu 2024 - Aulia Husnafa Navila; Annasya Regina Sitio; Sarah Diba; Yudha; Muhammad Prakoso Aji (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This research aims to analyze Okta Kumala Dewi's political communication strategy in the 2024 elections through Instagram. The theoretical framework used includes political communication, political communication strategy, and agenda setting, with qualitative methods based on content analysis and interviews. The results of the study show that Okta Kumala Dewi successfully combined formal and personal images in digital content, including posts about political activities, interactions with the community, and humanistic aspects of her daily life. Interaction data shows that humanistic content received more positive responses than formal political posts, emphasizing the importance of emotional closeness with young voters. This communication strategy aligns with the concept of participatory communication, which emphasizes direct public involvement. In conclusion, Instagram is an effective strategic space for building a political image, strengthening agenda setting, and creating emotional connections with the public. These findings underscore the role of social media as a contemporary political arena in Indonesia.